ANALISIS DAMPAK PERUBAHAN PTKP 2015 TERHADAP PERHITUNGAN PPH PASAL 21 PEGAWAI PADA PT PERKEBUNAN MITRA OGAN KEBUN MUBA - SUNANTO SUNANTO (JURNAL RISET TERAPAN AKUNTANSI, 2017)
The purpose of this research are determine how the calculation of Income Tax Point 21 before and after the change of Non-Taxable Income the new  and the effect of changes in Non-Taxable Income to the calculation ofannual Income Tax Point 21 employees in 2015. The type of data used are primary data and secondary data. The data was collected through interviews, observation, documentation and literature. The technicques of data analysis is quantitative technicques. The results showed that after the Non-Taxable Income new changes cause the number of employee Income Tax Point 21 is smaller. In addition, the calculation of the annual Income Tax Point 21 employees in 2015 after new Non-Taxable Income led to overpayment of Income Tax Point 21. For that is expectedPT Perkebunan Mitra Ogan Kebun MUBA should always be up to date on the development of tax legislation in force in Indonesia to avoid errors in the calculation and withholding tax payable causing harm to employees, companies and the State.